RESIDENTS' INTEGRITY IN THE CONCEPT OF HIJAB IN A SMALL TYPE OF URBAN ROW HOUSE (International Conference on Social and Islamic Studies, 2022)
The purpose of this study was to examine the behaviour of residents towards the application of the hijab concept to small-type dwellings in urban areas. Small-type houses are generally limited to the main rooms, namely the living room, bedroom, toilet, and kitchen. With this limited spatial layout, there is no clear separation between public space and private space. A house that functions to accommodate activities through architectural arrangements and the hijab as a teaching that regulates behaviour according to Islamic teachings are expected to work together to create an Islamic spatial pattern. This study uses a descriptive method to examine the integrity of the residents in applying the hijab concept to urban dwellings with limited land area. This study has two variables: (1) physical hijab, which consists of four indicators, namely layout, wall elements, doors, windows, and furniture; and (2) non-physical hijab, which consists of indicators of occupant behaviour or activities. The study's findings indicate that occupants' integrity is moderate, with the concept of hijab in urban dwellings manifested in (1) physical hijab with spatial planning that separates public and private spaces; and (2) non-physical hijab in the form of behaviour or manners that apply Islamic rules.